Rape and Constructions of Masculinity and Femininity: Remarks on Andreas Contribution in Politikon 6/2003 - Engels, Bettina (Politikon: The IAPSS Journal of Political Science, 2004)
With her paper Rape as a War Crime (Politikon 6/2003, p. 55-69), Andrea Theocharis has put an issue on the agenda, which has long been missing in Politikon’s discussions. I am grateful to Andrea for starting an important debate, which I would like to continue by giving some remarks to her contribution focusing on the gender constructionist dimension of rape in violent conflicts. Agreeing with Andrea, I will argue that rape and sexual violence are not only systematic and strategic weapons in violent conflicts but gendered crimes which cannot be analyzed appropriately without theorizing social and cultural constructions of masculinity and femininity. I will outline how gender-blind approaches fail to meet the issue of rape in violent conflicts. By mentioning some exemplary empirical figures, I will show that rape in violent conflicts is neither a new phenomena nor can it be considered a by-product of war. It must be emphasized that rape is not an act of sexuality but a crime against human physical and psychical integrity. I will discuss gender-sensitive approaches, which analyze rape in violent conflicts. Special attention will be paid to the view of rape as an act of male violence against women, which has also been outlined by Andrea. I will then focus on the construction of hegemonic masculinity and the widely ignored fact that also men are victims of rape and sexual torture in violent conflicts. I will conclude with emphasizing that constructions of femininity and masculinity are integral to violent conflicts in general and to rape and sexual violence in particular. If mainstream conflict analysis continues to ignore the dimensions of gender constructions, it will fail to meet its subject appropriately.